Análise de microRNAs exossomais como potenciais biomarcadores precoces da Lesão Renal Aguda induzida por lipopolissacarídeo em ratos - Silva, Carolina Carvalho Serres Da [UNIFESP] (2019)
Acute kidney injury (AKI) consists of the abrupt reduction of the glomerular filtration rate evidenced by increased serum creatinine and/or reduced urine output, compromising the electrolyte balance and the clearance of nitrogenous slags. The cause is multifactorial, and sepsis contributes to the high prevalence of AKI. It is known that the development and the delay in the identification of AKI is a risk factor for chronicity. In this way, its early detection is essential for trigger proper treatment strategies at a more opportune moment. Serum creatinine is not an optimal marker of renal dysfunction, since the elevation is detected late during AKI onset. microRNAs (miRs), a class of non-coding RNAs responsible for gene regulation, may be promising tools for the early detection of AKI. This class of molecules can be found in biological fluids within vesicles such as exosomes and microvesicles. Aim: To evaluate potential miRs that can be used as early biomarkers in sepsis-induced AKI. Methods: Male Wistar rats at 12 weeks of age undergoing intraperitoneal administration of lipopolysaccharides (LPS) at a dose of 7.5 mg/kg were used. Renal function was initially assessed by serum creatinine, with change detected 4 hr after LPS administration. In order to evaluate whether miRs could act as earlier biomarkers, blood samples were collected before and 2 hr after LPS infusion, and therefore before creatinine elevation. Exosomes in the serum were isolated and the total miRs were extracted for evaluation of the gene expression profile by the array PCR technique. Results: miR-181a-5p and miR-23b-3p showed higher expression in LPS-treated rats compared to the control animals (p<0.05). Bioinformatic studies showed that both miRs target molecules associated with carcinogenesis and to transcription factors that regulate genes related to proinflammatory cytokines. Conclusion: Considering that LPS activates transcription factors, leading to the production of proinflammatory cytokines, possible premature changes in serum levels of miR-181a-5p and miR-23b-3p may be able define earlier the sepsis-induced AKI.